Efficiency of Tributyltin Alkoxides in the Syntheses of L-Lactide and Poly(L-lactide) - Sureerat Khunmanee (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research examined methods to improve laboratory-scale synthesis of L-lactide (LLA) using tributyltin alkoxides (nC4H9)3SnOR (R = CH3, C2H5, nC3H7 and nC4H9) and conventional catalysts. (nC4H9)3SnOR were synthesized by the nucleophilic substitution of tributyltin chloride, (nC4H9)3SnCl. This process resulted in a colorless liquid (nC4H9)3SnOR which was purified by vacuum distillation and its identification was confirmed by 1H-NMR. The effects of types and amount of catalyst were investigated to produce LLA. Tributyltin butoxide, (nC4H9)3SnOnC4H9, gave the best results of the catalysts investigated in both polycondensation and thermal decomposition, giving a high % yield of LLA (80-90% crude, 65% purified) in high purity(99.5%) over a short reaction time (7.30 hrs). Besides, H2SO4 had highest activity on producing low molecular weight PLLA but it gave lowest yield of LLA (10%). Sn(Oct)2 was a strong racemization catalysts giving meso-lactide as an unwanted product even though it provided high yield of LLA. Ring opening polymerization of L-lactide (ROP) was carried out in a 20 ml vial which contained 10 g. of L-lactide. Comparison between the (nC4H9)3SnOR, Sn(OnC4H9)2 and Sn(Oct)2 showed that the highest molecular weight of PLLA was obtained when 0.1% mol Sn(Oct)2 was used as initiator at 140 ºC, 24 hrs, ( = 49,035) under the same condition. The results indicated that (nC4H9)3SnOnC4H9 gave lowest of molecular weight of PLLA because of the bulky groups of alkyl chain length causing the rate of polymerization decrease. In conclusion, (nC4H9)3SnOnC4H9 was an active catalyst for L-lactide, but it was not efficient enough for ring opening polymerization of L-lactide.